Flipped Learning in The Educational Process: Essence, Advantages, Limitations - Rakhmatov Ahmad Pirmukhammadovich (Indonesian Journal of Innovation Studies, 2022)
The article considers the essence of flipped learning and defines the features of the activities of the teacher and students in the process of implementing the flipped learning model. The didactic and technological aspects of the application of this teaching model at different levels of education are analyzed. The advantages and limitations of the use of flipped learning in the educational process are formulated.